Fate and free will : a defense of theological determinism - White, Heath, 1972- (University of Notre Dame Press, 2020)
"In Fate and Free Will, Heath White explores and defends a traditional view of God's relationship to creation that has in recent years fallen out of favor. White argues that theological determinism-the idea that God is directly responsible for every detail of history and existence-is relevant to concepts such as human responsibility, freedom, and justice; the meaning of life; and theodicy. Defending theological determinism from the perspective of traditional orthodox Christianity, White clarifies this view, positions it within scripture, and argues positively for it through considerations about divine attributes and via the idea of an ex nihilo creation. White addresses objections to theological determinism by presenting nuanced and insightful counterarguments. He asserts that theological determinism does not undermine practices of criminal punishment, destroy human responsibility, render life meaningless, or hinder freedom. While the book does not attempt to answer every dilemma concerning evil or hell, it effectively grapples with them. To make his case for theological determinism, White relies on theories of free will, moral responsibility, and a meaningful life. He uses clear commonsense language and vivid illustrations to bring to light the conditions of meaning and purpose in our lives and the metaphysics of God's relationship to the world. This original book will appeal to the philosophical community as well as students and scholars of theology"--